Passenger flow simulation in a hub airport: An application to the Barcelona International Airport - Fonseca i Casas, P.; Casanovas, J.; Ferran, X. (Simulation modelling practice and theory, 2014)
•Theoretical model that can be applied to the microsimulation of an airport.•Formal language to represent all the airport processes.•Representation of the passengers using intelligent agents.•Multidisciplinary teams working together.•Detailed microsimulation model of the Barcelona International Airport. This paper describes a conceptual model intended to be applied in a general approach to the micro-simulation of hub airports terminals. The proposed methodology is illustrated with the development of a simulation model originally intended to help in the design of the new terminal at Barcelona International Airport. This model represents in detail, among many other elements, passengers’ flows in the different areas of these complex facilities. Agent-based simulation techniques were included to represent the different actors’ behaviors, and a formal representation of the model using Specification and Description Language (SDL) was used to represent the complexity of all the system elements. To pre-process a diverse and considerable amount of raw data provided by airport designers and other sources to feed the simulation environment Flight Planner Manager was developed as a toolkit to parameterize the different model factors and to generate required specific input data. This project was conducted over 3years leading to the development of a system not only conceived to assess in the airport initial design process but also to constitute a recurrent decision taking instrument to dynamically optimize terminal management and operations.